Electrochemically Driven Nickel‐Catalyzed Enantioselective Hydro‐Arylation/Alkenylation of Enones - Zenghui Ye; Weiyuan Ma; Xi Zhang; Huaqing Liu; Fengzhi Zhang (Advanced Science)
Abstract Herein, the study reports the first electrochemical nickel‐catalyzed enantioselective hydro‐arylation/alkenylation of enones in an undivided cell with low‐cost electrodes in the absence of external reductants and supporting electrolytes. Aryl bromides/iodides/triflates or alkenyl bromides are employed as electrophiles for the efficient preparation of more than 56 valuable β‐arylated/alkenylated ketones in a simple manner (up to 97% yield, 97% ee). With the advantages of electrochemistry, excellent functional group tolerance and late‐stage modification of complex natural products and pharmaceuticals made the established protocol greener and more economic. Mechanism investigation suggests that a NiI/NiIII cycle may be involved in this electro‐reductive reaction rather than metal reductant driven Ni0/NiII cycle. Overall, the efficient electrochemical activation and turnover of the nickel catalyst avoid the drawbacks posed by the employment of stoichiometric amount of sensitive metal powder reductants.